ROE, EPS , DER dan Risiko terhadap Harga Saham serta Konsekuensinya terhadap Return Saham (Study pada Perusahaan sektor Manufaktur yang terdaftar di Bursa efek Indonesia Periode 2015 - 2017) - Yusuf Wijoyanto; Sri Sudarsi; Nungki Pradita (Jurnal Bisnis dan Ekonomi, 2018)
This study aims to examine the effect of Return on Equity (ROE), Earning per Share (EPS), Debt to Equity Ratio (DER), Risk to stock prices and its consequences for stock returns in manufacturing companies listed in the Indonesia Stock Exchange in 2015 - 2017. This research was conducted with using secondary data and the samples in this study used a purposive sampling method. The results of this study prove that ROE and DER has a negative and not significant effect on stock prices, EPS has a positive and significant effect on stock pricesBETA has a negative and significant effect on stock prices and stock prices have a negative and insignificant effect to stock returns. Adjusted R square model 1 is 0.981, this means that 98.1%